Tree above-ground biomass allometries for carbon stocks estimation in the Caribbean mangroves in Colombia - Yepes, Adriana (2016)
The distribution of carbon in "Blue Carbon" ecosystems such as mangroves is little known, when compared with the highly known terrestrial forests, despite its particular and recognized high productivity and carbon storage capacity. The objective of this study was to analyze the above ground biomass (AGB) of the species Rhizophora mangle and Avicennia germinans from the Marine Protected Area of Distrito de Manejo Integrado (DMI), Cispatá-Tinajones-La Balsa, Caribbean Colombian coast. With official authorization, we harvested and studied 30 individuals of each species, and built allometric models in order to estimate AGB. Our AGB results indicated that the studied mangrove forests of the DMI Colombian Caribbean was of 129.69 ± 20.24 Mg/ha, equivalent to 64.85 ± 10.12 MgC/ha. The DMI has an area of 8 570.9 ha in mangrove forests, and we estimated that the total carbon potential stored was about 555 795.93 Mg C. The equations generated in this study can be considered as an alternative for the assessment of carbon stocks in AGB of mangrove forests in Colombia; as other available AGB allometric models do not discriminate mangrove forests, despite being particular ecosystems. They can be used for analysis at a more detailed scale and are considered useful to determine the carbon storage potential of mangrove forests, as a country alternative to support forest conservation and emission reduction strategies. In general, the potential of carbon storage from Colombian Caribbean mangrove forests is important and could promote the country leadership of the “blue carbon” stored.